Tris-N-alkylpyridinium-functionalised cyclotriguaiacylene hosts as axles in branched [4]pseudorotaxane formation. Issue 6 (3rd June 2017) - Thorp-Greenwood, Flora L.; Brennan, Alexander D.; Oldknow, Samuel; Henkelis, James J.; Simmons, Katie J.; Fishwick, Colin W. G.; Hardie, Michaele J.
Abstract: A series of [4]pseudorotaxanes composed of three-way axle threads based on the cyclotriguaiacylene family of crown-shaped cavitands and three threaded macrocyclic components has been achieved. These exploit the strong affinity for electron-poor alkyl-pyridinium units to reside within the electron-rich cavity of macrocycles, in this case dimethoxypillar[5]arene (DMP). The branched [4]pseudorotaxane assemblies {(DMP)3 ∙ L } 3+, where L  =  N -alkylated derivatives of the host molecule (±)- tris -(isonicotinoyl)cyclotriguaiacylene, were characterised by NMR spectroscopy and mass spectrometry, and an energy-minimised structure of {(DMP)3 ∙( tris -( N -propyl-isonicotinoyl)cyclotriguaiacylene)} 3+ was calculated. Crystal structures of N -ethyl-isonicotinoyl)cyclotriguaiacylene hexafluorophosphate and N -propyl-isonicotinoyl)cyclotriguaiacylene hexafluorophosphate each show 'hand-shake' self-inclusion motifs occurring between the individual cavitands. Abstract :